A Unified Framework for Estimating Preferences for Schools and Neighborhoods - Patrick Bayer; Fernando Ferreira; Robert McMillan (Yale University, Economic Growth Center, 2003)
This paper sets out a framework for estimating household preferences over a broad range of housing and neighborhood characteristics, some of which are determined by the way that households sort in the housing market. This framework brings together the treatment of heterogeneity and selection that has been the focus of the traditional discrete choice literature with a clear strategy for dealing with the correlation of unobserved neighborhood quality with both school quality and neighborhood sociodemographics. We estimate the model using rich data on a large metropolitan area, drawn from a restricted version of the Census. The estimates indicate that, on average, households are willing to pay an additional one percent in house prices – substantially lower than in prior work – when the average performance of the local school is increased by 5 percent. There is also evidence of considerable preference heterogeneity. We also show that the full capitalization of school quality into housing prices is typically 70-75 percent greater than the direct effect as the result of a social multiplier, neglected in the prior literature, whereby increases in school quality also raises prices by attracting households with more education and income to the corresponding neighborhood.
Keywords: D58; H0; H4; H7; I2; R21; R31; 330; Capitalization; Local Public Goods; School Quality; Discrete Choice Models; Hedonic Price Regression; Education Demand; Präferenztheorie; Lokale öffentliche Güter; Schule; Wohnstandort; Hedonischer Preisindex; San Francisco Bay (Region)